La verità nella libertà: La natura dell'uomo, la ragione e la libertà creativa - Gentile, Andrea (Miscellanea francescana, 2017)
Each of us is an unrepeatable individual. Everyone is a universe. "The human soul is an individual in the realm of spirits, which he feels according to his singular constitution; is a peculiar feature that is manifested by the whole dark background of our interiority, whose inexpressible depths sleep as unknown kings". Everyone raises a great or a small wave. Our existence, in its concreteness, unpreparedness and singularity, is always a particular existence, unique, unrepeatable and unmistakable. Existence is "indisputable" in its authenticity, it is not a fact, but it is a personal matter. From this it follows that even man is not a fact: he is able to be. His free choice lies in the recognition and acceptance of the only possibility that is the particular "situation" where he fi nds himself. Man is not able to be and is unable to become but what is in his authenticity, in his "being himself" and in expressing his creative autonomy. (English)